2003
DOI: 10.1097/01.ju.0000095475.12515.5e
|View full text |Cite
|
Sign up to set email alerts
|

Solid Renal Tumors: An Analysis of Pathological Features Related to Tumor Size

Abstract: As tumor size increased there was a significant increase in the odds of having a malignant compared to a benign tumor, clear cell compared to papillary RCC and high grade compared to low grade malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

31
536
7
33

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 945 publications
(607 citation statements)
references
References 16 publications
31
536
7
33
Order By: Relevance
“…The greatest frequency of benign lesions in renal tumors is smaller than 3 cm, as previously published (12)(13)(14). This study concludes that benign lesion sizes are much larger than those reported in other studies.…”
Section: Discussioncontrasting
confidence: 47%
“…The greatest frequency of benign lesions in renal tumors is smaller than 3 cm, as previously published (12)(13)(14). This study concludes that benign lesion sizes are much larger than those reported in other studies.…”
Section: Discussioncontrasting
confidence: 47%
“…Ten complications (12%) were noted (Supplementary table 3 Current guidelines recommend surgical extirpation for all renal cortical masses despite the finding that upwards of 30% of these lesions are benign or of low malignant potential 19 . Over the past decade, PCA has emerged as an effective, less morbid, alternative treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…1 Furthermore, recent surgical series have reported that up to 20% of small renal masses (tumors less than 4 cm) are benign and only 20% to 25% have potentially aggressive features. [2][3][4] However, despite an earlier detection of renal masses, cancer-specific deaths caused by renal cell carcinoma (RCC) have not concordantly declined, suggesting that some patients may be overtreated from aggressive surgical management. 5 Select patients may benefit from nonextirpative surgery with treatment modalities such as active surveillance or thermal ablation.…”
Section: Introductionmentioning
confidence: 99%